Chromium oxyhydroxide adsorbent for selective bromine extraction and preparation method of chromium oxyhydroxide adsorbent
By conducting hydrothermal reaction in a mixed system including soluble chromium salt, reducing agent, mineralizer and water, a hydroxychromium oxide adsorbent with high crystallinity and excellent stability is prepared, which solves the problems of harsh synthesis conditions of hydrated chromium oxide and amorphous structure of the product in the prior art, and achieves efficient bromide ion adsorption selectivity.
Patent Information
- Application Number
- CN202510158832.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-13
- Publication Date
- 2025-04-29
AI Technical Summary
In the prior art, the synthesis conditions of hydrated chromium oxide are harsh, the products are often amorphous structures, mixed crystal forms, and the agglomeration phenomenon is serious, which limits its application value.
The first hydrothermal reaction is performed in a mixed system including soluble chromium salt, reducing agent, mineralizer and water to obtain a hydrated chromium oxide precursor, and a second hydrothermal reaction is performed in a strong acidic solution with pH ≤3 to prepare a hydroxychromium oxide adsorbent with high crystallinity and excellent stability.
A pure tripartite phase α-CrOOH adsorbent with high crystallinity and excellent stability was prepared, with good adsorption selectivity and modification, and is suitable for selective extraction of bromine in brine.
Smart Images

Figure CN119898818A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of new chemical materials, and in particular relates to a chromium hydroxide oxide adsorbent for selective bromine extraction and a preparation method thereof. Background Art
[0002] The application of bromine and its compounds in the fields of chemical industry, medicine, new energy, etc. has promoted the development of various industries. At present, with the continuous deepening of the research on the comprehensive development and utilization of brine resources, how to separate and extract the rare element bromine in brine in a green and efficient way has become a hot topic of research at home and abroad. The distribution of bromine resources is mostly in the form of bromide in salt lake brine and underground brine. Although the reserves are considerable, the concentration of bromine in brine is usually low, and the composition of natural brine is complex, especially containing a large amount of chlorine, iodine and other elements that coexist with bromine and have similar properties, which brings great difficulties to the separation, purification and deep processing of bromine products. The main methods for extracting bromine resources that have been developed include air blowing method, precipitation method, ion exchange method, etc. Although these technologies can achieve effective separation and recovery of bromine resources, they have certain limitations in the selective separation of bromine. In view of the premise of green and sustainable brine mining, the adsorption method has become one of the most promising methods due to its advantages of low cost, simple operation, environmental friendliness and no secondary pollution. Therefore, how to utilize the differences between bromine and other elements to develop adsorption materials with good selectivity, high separation efficiency and applicability to brine systems is a key scientific problem that needs to be solved.
[0003] Chromium-based adsorbents (hydrated chromium oxide Cr2O3·nH2O) have the advantages of stable physicochemical properties, rich crystal structures, good selectivity, strong modifiability, and high reactivity and affinity for anionic groups, making them ideal materials for extracting bromine from brine. It is reported that the main forms of hydrated chromium oxide known so far are: α-CrOOH, β-CrOOH, γ-CrOOH, Cr(OH)3, Cr(OH)3·3H2O. Different preparation methods will affect factors such as crystal structure, physicochemical properties, morphology and pore size. At present, the main methods for synthesizing hydrated chromium oxide include chemical precipitation, hydrothermal method, and hydrogen reduction. Among them, the Cr2O3·nH2O obtained by chemical precipitation is mostly amorphous, with mixed crystal forms and serious particle agglomeration, which seriously limits its application value in various fields.
[0004] Some researchers used a mixed solution of CrO3 and polyvinyl alcohol as a precursor, and obtained nanorod-shaped CrOOH after reacting in a sealed reactor for a certain period of time. The product prepared by the hydrothermal temperature of this method is α-CrOOH at 400°C, and the product obtained at 380°C is a mixture of α-CrOOH and β-CrOOH. The reaction temperature is relatively high, and CrOOH with a single crystal form is not easy to obtain. Some researchers added a hexavalent chromium salt solution to the reaction device, introduced a protective gas, and then heated it in a sealed manner. After reaching the reaction temperature, a reducing gas was introduced for a period of reaction to obtain a reduced slurry, and after solid-liquid separation, a bottom-centered orthorhombic structure of hydroxy chromium oxide was obtained. The main component of the product prepared by this method is α-CrOOH, but its XRD spectrum has other impurity peaks, and a single component α-CrOOH cannot be obtained. In summary, the synthesis conditions of α-CrOOH in the prior art are extremely harsh (T>400°C); the synthesized products α-CrOOH and β-CrOOH / γ-CrOOH are mixed together and cannot be effectively separated; the agglomeration phenomenon is serious and the specific surface area is small. Summary of the invention
[0005] The main purpose of the present invention is to provide a chromium hydroxide oxide adsorbent for selective bromine extraction and a preparation method thereof, so as to overcome the shortcomings of the prior art.
[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:
[0007] One aspect of the present invention provides a method for preparing a chromium hydroxide oxide adsorbent for selective bromine extraction, which comprises: subjecting a mixed system including a soluble chromium salt, a reducing agent, a mineralizer and water to a first hydrothermal reaction to obtain a hydrated chromium oxide precursor; and subjecting the hydrated chromium oxide precursor to a second hydrothermal reaction in a strongly acidic solution with a pH value of ≤3 to prepare a chromium hydroxide oxide adsorbent.
[0008] Another aspect of the present invention provides a chromium oxyhydroxide adsorbent prepared by the above preparation method.
[0009] Another aspect of the present invention also provides the use of the aforementioned chromium oxyhydroxide adsorbent in adsorbing bromide ions.
[0010] Another aspect of the present invention provides a method for removing bromide ions in an aqueous system, comprising: using the aforementioned chromium hydroxide oxide adsorbent to adsorb bromide ions in the aqueous system.
[0011] Compared with the prior art, the present invention has at least the following beneficial effects:
[0012] (1) The preparation method of the present invention is based on the physicochemical properties of chromium-based materials. By controlling the hydrothermal synthesis conditions, a chromium-based adsorbent nanomaterial with high crystallinity and excellent stability is obtained. This method not only solves the problems of low activity, short service life, and easy agglomeration of existing chromium-based adsorbents, but also retains the excellent hydrophilicity, pore structure and surface activity of chromium hydroxide to the maximum extent.
[0013] (2) The chromium hydroxide adsorbent prepared by the present invention is a pure trigonal phase α-CrOOH with a developed microporous and mesoporous structure, rich surface active sites and functional groups, and a multi-hydroxy structure on the surface of the matrix that can effectively adsorb bromide ions. However, due to the limited structure and other properties, it basically does not adsorb iodine ions. It has good adsorption selectivity and strong modifiability. In the later stage, it can be used as a stable inorganic skeleton to load various effective active substances, so as to achieve efficient applications in the fields of concentrated seawater / brine bromine extraction, groundwater bromine removal, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0015] Figure 1 The CrO prepared in Example 1 of the present invention x (OH) 3-2x XRD pattern of the precursor;
[0016] Figure 2a The CrO prepared in Example 1 of the present invention x (OH) 3-2x SEM image of the precursor at 5 μm;
[0017] Figure 2b is a SEM image of the α-CrOOH adsorbent prepared in Example 1 of the present invention at 500 nm;
[0018] Figure 3 is the XRD pattern of the α-CrOOH adsorbent prepared in Example 1 of the present invention;
[0019] Figure 4 is an EDS characterization diagram of the α-CrOOH adsorbent prepared in Example 2 of the present invention;
[0020] Figure 5a The CrO prepared in Example 3 of the present invention x (OH) 3-2x SEM image of the precursor at 5 μm;
[0021] Figure 5b is a SEM image of the α-CrOOH adsorbent prepared in Example 3 of the present invention at 500 nm;
[0022] Figure 6 is the FT-IR image of the α-CrOOH adsorbent prepared in Example 4 of the present invention;
[0023] Figure 7 is a pore size distribution image of the α-CrOOH adsorbent prepared in Example 4 of the present invention;
[0024] Figure 8 This is a BET comparison chart of the α-CrOOH adsorbent prepared in Example 5 of the present invention and the α-CrOOH of the published invention patent;
[0025] Fig. 9 This is the XRD pattern of the α-CrOOH adsorbent prepared in Example 5 of the present invention after being immersed in pure water, HCl, NaOH, CH3O, and DMF solutions for 7 days;
[0026] Fig.10 This is a diagram showing the adsorption effect of α-CrOOH adsorbents prepared in Examples 1-7 of the present invention on bromide ions and iodide ions. DETAILED DESCRIPTION
[0027] In view of the problems existing in the above-mentioned prior art, the inventors of the present invention have conducted extensive and in-depth research and provided a chromium hydroxide oxide adsorbent for selective bromine extraction and a preparation method thereof. The chromium hydroxide oxide adsorbent nanomaterial with high crystallinity and excellent stability is obtained by controlling the hydrothermal synthesis conditions based on the physicochemical properties of chromium-based materials.
[0028] Chromium-based adsorbents mainly refer to adsorption materials with Cr(III) as the main component. Their chemical structures are mainly chromium hydroxide structure and chromium oxide hydroxyl structure. The expression is generally "Cr2O3·nH2O", mainly including Cr(OH)3, α-CrOOH, β-CrOOH, γ-CrOOH, Cr2O3 and other types.
[0029] The technical solution, its implementation process and principle will be further explained as follows.
[0030] As one aspect of the technical solution of the present invention, a method for preparing a chromium hydroxide oxide adsorbent for selective bromine extraction is provided, comprising: subjecting a mixed system including a soluble chromium salt, a reducing agent, a mineralizer and water to a first hydrothermal reaction to obtain a hydrated chromium oxide precursor; and subjecting the hydrated chromium oxide precursor to a second hydrothermal reaction in a strongly acidic solution with a pH value of ≤3 to prepare a chromium hydroxide oxide adsorbent.
[0031] In some more specific embodiments, the preparation method specifically comprises: mixing the soluble chromium salt, the reducing agent, the mineralizer and water uniformly, adjusting the pH to 4.5-14, and then performing a first hydrothermal reaction at 120°C-260°C to obtain a hydrated chromium oxide precursor CrO x (OH) 3-2x , where x ranges from 0 to 1.
[0032] In some embodiments, the temperature of the first hydrothermal reaction is 120°C to 260°C.
[0033] In some preferred embodiments, the temperature of the first hydrothermal reaction is 180° C. to 240° C. The hydrated chromium oxide precursor obtained under this temperature range is a 3D nanoflower-like microsphere structure.
[0034] In some embodiments, the first hydrothermal reaction is carried out for 2 to 24 hours.
[0035] In some embodiments, the mass ratio of the soluble chromium salt, the reducing agent and the mineralizer is (1-1.5): (1.2-0.2): (0.1-0.5).
[0036] In some preferred embodiments, the pH value of the mixed solution in the first hydrothermal reaction is 6-9, the hydrated chromium oxide particles prepared under weakly acidic, neutral and weakly alkaline conditions are small, and the specific surface area is larger than that under alkaline conditions; the prepared hydroxy chromium oxide has a better adsorption effect.
[0037] In some embodiments, the soluble chromium salt includes a hexavalent chromium salt, and the hexavalent chromium salt includes any one or a combination of two or more of chromic acid, potassium chromate, potassium dichromate, ammonium chromate, ammonium dichromate, chromium chromate, chromic anhydride, sodium chromate, sodium dichromate, etc., but is not limited thereto.
[0038] In some embodiments, the reducing agent includes any one or a combination of two or more of starch, urea, ascorbic acid, PVA, sodium persulfide, ethylene glycol, acetic acid, citric acid, methanol, anhydrous ethanol, etc., but is not limited thereto. The reducing agent used in the present invention is preferably a carbon-based reducing agent, which has the advantages of low cost, high reduction rate, and green environmental protection. In the present invention, different types of reducing agents will have a slight effect on the morphology and specific surface area of the hydrated chromium oxide precursor, and have little effect on the prepared hydroxyl chromium oxide.
[0039] In some embodiments, the mineralizer includes any one or a combination of two or more of sodium carbonate, sodium bicarbonate, sodium hydroxide, etc., but is not limited thereto.
[0040] In some more specific embodiments, the preparation method specifically includes: after uniformly mixing the hydrated chromium oxide precursor and the strong acid solution, performing a second hydrothermal reaction at 160° C. to 240° C., thereby preparing the chromium oxide hydroxy adsorbent.
[0041] In some embodiments, the temperature of the second hydrothermal reaction is 160°C to 240°C.
[0042] In some preferred embodiments, the temperature of the second hydrothermal reaction is 200° C. to 240° C., which can make the obtained chromium oxyhydroxide adsorbent have higher crystallinity.
[0043] In some embodiments, the second hydrothermal reaction time is 2 to 24 hours.
[0044] In some preferred embodiments, the second hydrothermal reaction time is 2 to 12 hours.
[0045] In some embodiments, the pH of the strongly acidic solution is 0.1-3.
[0046] In some embodiments, the solid-liquid ratio of the hydrated chromium oxide precursor to the strong acid solution is 0.01:1 to 0.1:1.
[0047] In some embodiments, the strong acid solution includes at least any one of hydrochloric acid, sulfuric acid, nitric acid, perchloric acid, chromic acid, etc., but is not limited thereto.
[0048] In some more specific embodiments, the preparation method may include the following steps:
[0049] (1) Preparation of CrO x (OH) 3-2x Precursor: Dissolve soluble chromium salt, reducing agent and mineralizer in deionized water, stir thoroughly and adjust pH to 4.5-14, transfer the mixed solution to a polytetrafluoroethylene reactor, perform hydrothermal reaction at 120-260℃ for 2-24h, and obtain CrO after solid-liquid separation. x (OH) 3-2x Precursor, where x is 0-1;
[0050] (2) Prepare a strong acid solution with a pH of 0.1 to 3, and then add CrO x (OH) 3-2x The precursor and the strong acid solution are ultrasonically mixed in a polytetrafluoroethylene liner, and a hydrothermal reaction is carried out at 160°C to 240°C for 2 to 24 hours to complete the reaction, wherein the reaction temperature is preferably 200°C to 240°C and the reaction time is 2 to 12 hours;
[0051] (3) After the hydrothermal reaction is completed, the obtained slurry is separated, and the filter cake is fully washed with secondary water and anhydrous ethanol until the pH value of the filtrate is neutral. The filter cake is dried at 60° C. to obtain the chromium hydroxide adsorbent.
[0052] Specifically, the reaction mechanism for preparing the chromium oxyhydroxide adsorbent is as follows:
[0053] Under high temperature conditions, Cr(VI) in the solution is reduced to Cr(III). At the same time, the pH of the solution increases, and Cr(III) gradually hydrolyzes and crystallizes to form a hydrated chromium oxide precursor; the main component of the hydrated chromium oxide precursor is CrOx(OH) 3-2x , which is a mixture of Cr(OH)3 and CrOOH. During the hydrothermal process, strong acidic conditions will promote the growth of certain crystal faces, resulting in a crystal phase transition: Cr(OH)3→α-CrOOH.
[0054] As another aspect of the technical solution of the present invention, a chromium oxyhydroxide adsorbent prepared by the above-mentioned preparation method is provided.
[0055] The chromium hydroxide oxide adsorbent synthesized by the present invention is a nanomaterial with good dispersibility, uniform particle size distribution, and independent regular hexagonal flake morphology; its crystal state is good, there is no obvious impurity peak, and the crystal phase of the nanomaterial is pure, which is a pure trigonal phase α-CrOOH. The preparation method of the present invention can accurately control a single α-CrOOH crystal structure, and its α-CrOOH has microporous and mesoporous structures, and the surface of α-CrOOH has abundant hydroxyl group active sites. However, due to the inherent properties of nanomaterials, the flake-like chromium hydroxide oxide adsorbent will inevitably show partial accumulation.
[0056] Furthermore, the mass fraction of chromium in the chromium-based adsorbent is 60.5-68.6%.
[0057] Furthermore, the crystal form of the chromium-based adsorbent mainly includes trigonal α-CrOOH.
[0058] Furthermore, the micropores contained in the chromium oxyhydroxide adsorbent are mainly caused by the properties of the material itself, and the pore size distribution range is 1-2 nm. The mesopores are mainly caused by the gaps between the materials, and the pore size distribution range is 12.97-14.27 nm.
[0059] Furthermore, the particle size of the chromium-based adsorbent is 50 to 100 nm.
[0060] Furthermore, the specific surface area of the chromium-based adsorbent is 53.68 to 55.04 m 2 / g.
[0061] Furthermore, the morphology of the chromium-based adsorbent includes regular hexagonal flakes.
[0062] As another aspect of the technical solution of the present invention, it also provides the use of the aforementioned chromium hydroxide oxide adsorbent in the adsorption of bromide ions.
[0063] Furthermore, the aforementioned chromium oxyhydroxide adsorbent is used in the field of extracting bromine from concentrated seawater / brine or removing bromine from groundwater.
[0064] As another aspect of the technical solution of the present invention, a method for removing bromide ions in an aqueous system is also provided, comprising: using the chromium oxyhydroxide adsorbent to adsorb bromide ions in the aqueous system. The aqueous system may be salt lake brine, industrial wastewater, seawater or other types of aqueous solutions.
[0065] One embodiment of the present invention provides a method for extracting bromine from brine, comprising: contacting the chromium oxyhydroxide adsorbent with brine to adsorb bromide ions in the brine.
[0066] In summary, the present invention utilizes an acidic system hydrothermal method to obtain a high-purity single-crystal chromium oxide adsorbent at an appropriate temperature by controlling the crystal form, which can effectively remove bromide ions in an aqueous solution.
[0067] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.
[0068] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the art can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially. The commercial selection of the remaining raw materials and instruments not mentioned are all conventional selections and do not involve the core technical means of the present invention.
[0069] Example 1
[0070] (1) 12.35 g of chromic anhydride and 3.71 g of starch were weighed and dispersed in 150 mL of deionized water, and then dispersed evenly by ultrasonication. 5 g of sodium carbonate was added and the pH value was adjusted to 6. The prepared mixed solution was transferred to a 200 mL stainless steel high-temperature reactor, heated to 190°C and maintained for 12 h. After the reaction was completed, it was naturally cooled to room temperature, and the mixture was separated into solid and liquid, and CrO was obtained after being fully washed with water and dried. x (OH) 3-2xThe XRD pattern of the precursor powder is as follows Figure 1 As shown in the SEM images Figure 2a shown.
[0071] (2) 2g CrO x (OH) 3-2x The powder is evenly dispersed into 150mL1 mol·L -1 concentrated sulfuric acid solution; after ultrasonic treatment for 15 minutes, the mixed solution was transferred to a 200 mL stainless steel high-temperature reactor, heated to 220°C, reacted for 6 hours, cooled to room temperature, and the solid phase was fully washed with ethanol and pure water, and then dried in an oven at 60°C for 12 hours to obtain a chromium hydroxide adsorbent, the SEM image of which is shown in FIG. Figure 2b As shown in the figure, it can be seen that the chromium hydroxide adsorbent has a regular hexagonal flake shape. After measurement, the particle size of most particles is 50-100nm, which belongs to the category of nanomaterials. Figure 3 As shown, the characteristic diffraction peak of the chromium hydroxide adsorbent is highly consistent with α-CrOOH (PDF#98-001-6703), which is a simple trigonal structure and belongs to the space group R-3m; and no characteristic peaks of other substances appear, indicating that the product prepared in Example 1 is a single α-CrOOH adsorbent.
[0072] Accurately weigh 0.05g of chromium hydroxide powder and 1000mg·L -1 Mix the KBr and KI solutions (in terms of Br ions and I ions) with 1 mol·L -1 HCl and 1 mol·L -1 After adjusting the pH to 2 with NaOH, the mixture was shaken at 160 rpm for 6 h in a constant temperature shaker. After the adsorption experiment was completed, the mixture was filtered using a microporous membrane with a pore size of 0.22 μm, and the filtered clear solution was diluted and finally analyzed and determined using an ion chromatograph. The experimental results are shown in Fig.10 .
[0073] Example 2
[0074] (1) 17.55 g of sodium chromate was dissolved in 30 mL of deionized water to obtain solution 1; 1 g of polyvinyl alcohol (PVA) was dispersed in 30 mL of deionized water, dissolved completely in a water bath at 80°C, and cooled to room temperature to obtain solution 2; solution 1 was added dropwise to solution 2, 2 g of sodium bicarbonate was added and the pH value was adjusted to 8, and the mixture was stirred for 3 h before being transferred to a 100 mL stainless steel high-temperature reactor, heated to 180°C and maintained for 10 h. After the reaction was completed, the mixture was naturally cooled to room temperature, and CrO was obtained after solid-liquid separation, washing, and drying. x (OH) 3-2x Precursor powder.
[0075] (2) 1g CrO x (OH) 3-2x The powder was evenly dispersed into 50mL 2mol·L -1 After ultrasonic treatment for 15 min in chromic acid solution, the mixed solution was transferred to a 100 mL stainless steel high temperature reactor, heated to 200 ° C, reacted for 6 h, cooled to room temperature, and the solid phase was fully washed with ethanol and pure water, and dried in an oven at 60 ° C for 12 h to obtain α-CrOOH. Its EDS characterization diagram is shown in the figure Figure 4 As shown by Figure 4 It can be seen from the EDS image that the material is composed of Cr and O, with contents of 68.6% and 31.4%, respectively.
[0076] Accurately weigh 0.05g of chromium hydroxide powder and 1000mg·L -1 Mix the KBr and KI solutions (in terms of Br ions and I ions) with 1 mol·L -1 HCl and 1 mol·L -1 After adjusting the pH to 3 with NaOH, the mixture was shaken at 160 rpm for 12 h in a constant temperature shaker. After the adsorption experiment was completed, the mixture was filtered using a microporous membrane with a pore size of 0.22 μm. The filtered clear solution was diluted and finally analyzed and determined using an ion chromatograph. The experimental results are shown in Fig.10 .
[0077] Example 3
[0078] (1) 20 g potassium chromate and 2 g urea were dissolved in 150 mL deionized water, and then 3 g potassium carbonate was added and the pH value was adjusted to 14. The prepared mixed solution was transferred to a 200 mL stainless steel high-temperature reactor, heated to 220 °C and maintained for 24 h. After the reaction was completed, CrO was obtained by solid-liquid separation, washing and drying. x (OH) 3-2x The SEM image of the precursor powder is shown in 5a.
[0079] (2) 3g CrO x (OH) 3-2x The powder was evenly dispersed in 60 mL of 1.5 mol·L -1 After ultrasonication for 15 min, the mixed solution was transferred to a 100 mL stainless steel reactor and heated to 240 °C. After reacting for 12 h, solid-liquid separation was performed. After washing and drying, α-CrOOH adsorbent was obtained. Its SEM image is shown in Figure 5b shown.
[0080] Accurately weigh 0.05g of chromium hydroxide powder and 1000mg·L -1 Mix the KBr and KI solutions (in terms of Br ions and I ions) with 1 mol·L-1 HCl and 1 mol·L -1 After adjusting the pH to 4 with NaOH, the mixture was shaken at 180 rpm for 24 h in a constant temperature shaker. After the adsorption experiment was completed, the mixture was filtered using a microporous membrane with a pore size of 0.22 μm, and the filtered clear solution was diluted and finally analyzed and determined using an ion chromatograph. The experimental results are shown in Fig.10 .
[0081] Example 4
[0082] (1) 28.44 g of sodium dichromate and 3.71 g of ascorbic acid were dissolved in 150 mL of deionized water, and 1 g of sodium bicarbonate was added, followed by adjusting the pH value to 4. The prepared solution was transferred to a 200 mL stainless steel high-temperature reactor, heated to 160°C and maintained for 6 h. After the reaction was completed, the mixture was naturally cooled to room temperature, and the mixture was subjected to solid-liquid separation, and CrO was obtained after being fully washed with water and dried. x (OH) 3-2x Precursor powder.
[0083] (2) 5g CrO x (OH) 3-2x The powder was evenly dispersed into 120 mL 6 mol·L -1 After 15 minutes of ultrasonic treatment in hydrochloric acid solution, the mixed solution was transferred to a 200 mL stainless steel high temperature reactor, heated to 180°C, reacted for 24 hours, cooled to room temperature, and the solid phase was fully washed with ethanol and pure water, and dried in a 60°C oven for 12 hours to obtain α-CrOOH adsorbent. Its FT-IR image is shown in the figure Figure 6 As shown, it can be seen that 3417.3 and 1629.9cm -1 The pore size distribution diagram is shown in Figure 2, which corresponds to the stretching vibration of the single-bond -OH group and the bending vibration of the water molecule, which are characteristic bands of α-CrOOH, indicating that the surface of α-CrOOH has abundant hydroxyl group active sites. Figure 7 As shown, it can be seen that the pore size is mainly distributed around 16 nm, and there is a narrow peak at 1.5 nm, indicating that the adsorbent has microporous and mesoporous structures.
[0084] Accurately weigh 0.02g of chromium hydroxide powder and 1000mg·L -1 Mix the KBr and KI solutions (in terms of Br and I ions) and use 1 mol·L -1 HCl and 1 mol·L -1 After adjusting the pH to 6 with NaOH, the mixture was shaken at 160 rpm for 12 h in a constant temperature shaker. After the adsorption experiment was completed, the mixture was filtered using a microporous membrane with a pore size of 0.22 μm. The filtered clear solution was diluted and finally analyzed and determined using an ion chromatograph. The experimental results are shown in Fig.10.
[0085] Example 5
[0086] (1) 8 g of ammonium chromate, 14 g of sodium dichromate and 3.92 g of ethylene glycol were dissolved in 150 mL of deionized water, and then 1 g of potassium carbonate and 0.5 g of potassium hydroxide were added to adjust the pH of the solution to 14. The prepared mixed solution was transferred to a 200 mL stainless steel high-temperature reactor, heated to 260 ° C and maintained for 2 h. After the reaction was completed, CrO was obtained by solid-liquid separation, washing and drying. x (OH) 3-2x Precursor powder.
[0087] (2) 4.5 g CrO x (OH) 3-2x The powder was evenly dispersed in 60 mL of 1.5 mol·L -1 After ultrasonic treatment for 15 min in a perchloric acid solution, the mixed solution was transferred to a 100 mL stainless steel reactor and heated to 160 °C. After reacting for 12 h, solid-liquid separation was performed, and the α-CrOOH adsorbent was obtained after washing and drying.
[0088] Figure 8 They are BET comparison images of α-CrOOH of Example 5 (sample 1) and the published invention patent (sample 2). The α-CrOOH synthesized under the experimental conditions has a larger specific surface area, which is 53.68 m 2 / g. Sample 1 was immersed in pure water, HCl, NaOH, CH3O, and DMF solvents for 7 days, and its XRD patterns were as follows: Fig. 9 As shown, it can be seen that the characteristic peaks remain basically consistent, indicating that the α-CrOOH adsorbent synthesized under the experimental conditions has good stability.
[0089] Accurately weigh 0.04g of chromium hydroxide powder and 1000mg·L -1 Mix the KBr and KI solutions (in terms of Br ions and I ions) with 1 mol·L -1 HCl and 1 mol·L -1 After adjusting the pH to 4 with NaOH, the mixture was shaken at 180 rpm for 24 h in a constant temperature shaker. After the adsorption experiment was completed, the mixture was filtered using a microporous membrane with a pore size of 0.22 μm, and the filtered clear solution was diluted and finally analyzed and determined using an ion chromatograph. The experimental results are shown in Fig.10 .
[0090] Example 6
[0091] (1) 14.12 g potassium chromate, 10.36 g chromic anhydride and 15.03 g citric acid were dissolved in 120 mL deionized water, 2 g sodium bicarbonate was added and the solution was mixed evenly, and the pH of the solution was adjusted to 9; the prepared mixed solution was transferred to a 200 mL stainless steel high temperature reactor, heated to 200 ° C and maintained for 8 h. After the reaction was completed, CrO was obtained by solid-liquid separation, washing and drying. x (OH) 3-2x Precursor powder.
[0092] (2) 1.5 g CrO x (OH) 3-2x The powder was evenly dispersed in 60 mL of 4.5 mol·L -1 In the chromic acid solution, after ultrasonication for 30 minutes, the mixed solution was transferred to a 100 mL stainless steel reactor, heated to 210°C, reacted for 8 hours, and then solid-liquid separation was performed. After washing and drying, the chromium hydroxide adsorbent was obtained.
[0093] Accurately weigh 0.025g of chromium hydroxide powder and 1000mg·L -1 Mix the KBr and KI solutions (in terms of Br ions and I ions) with 1 mol·L -1 HCl and 1 mol·L -1 After adjusting the pH to 9 with NaOH, the mixture was shaken at 180 rpm for 24 h in a constant temperature shaker. After the adsorption experiment was completed, the mixture was filtered using a microporous filter membrane with a pore size of 0.22 μm, and the filtered clear solution was diluted and finally analyzed and determined using an ion chromatograph. The experimental results are shown in Fig.10 .
[0094] Example 7
[0095] (1) 12.98 g of sodium dichromate was dissolved in 150 mL of deionized water, and then 7.50 mL of anhydrous ethanol was added. After mixing, 2.8 g of sodium hydroxide and 0.3 g of sodium carbonate were added and the pH was adjusted to 10. The prepared mixed solution was transferred to a 200 mL stainless steel high-temperature reactor, heated to 170 °C and maintained for 16 h. After the reaction was completed, CrO was obtained by solid-liquid separation, washing and drying. x (OH) 3-2x Precursor powder.
[0096] (2) 3g CrO x (OH) 3-2x The powder was evenly dispersed in 30 mL 8 mol·L -1 After ultrasonic treatment for 60 min in a nitric acid solution, the mixed solution was transferred to a 50 mL stainless steel reactor and heated to 170 ° C. After reacting for 2 h, solid-liquid separation was performed, and the chromium hydroxide adsorbent was obtained after washing and drying.
[0097] Accurately weigh 0.01g of chromium hydroxide powder and 1000mg·L -1 Mix the KBr and KI solutions (in terms of Br ions and I ions) with 1 mol·L -1 HCl and 1 mol·L -1 After adjusting the pH to 12 with NaOH, the mixture was shaken at 180 rpm for 24 h in a constant temperature shaker. After the adsorption experiment was completed, the mixture was filtered using a microporous membrane with a pore size of 0.22 μm, and the filtered clear solution was diluted and finally analyzed and determined using an ion chromatograph. The experimental results are shown in Fig.10 .
[0098] Example 8
[0099] The basic steps are the same as those of Example 7, except that the pH of the mixed solution in step (1) is 14.
[0100] In this embodiment, the morphology of the hydrated chromium oxide obtained by the first hydrothermal reaction is a flower ball-like structure self-assembled from extremely thin and wide lamellar structures; after the second hydrothermal reaction, the particle size of the obtained hydroxyl chromium oxide increases, and the thickness of the hexagonal lamellar structure also increases. Compared with Example 7, the particle size and thickness of the hydroxyl chromium oxide obtained in this embodiment increase, but the specific surface area decreases, and the adsorption effect on bromine decreases.
[0101] Comparative Example 1
[0102] The basic steps are the same as those in Example 1, except that the solution system in step (2) is 2 mol·L -1 Acetic acid solution.
[0103] In this embodiment, since the acidity of the solution system is relatively weak when the hydrated chromium oxide precursor undergoes a crystal transformation, the structure of the hydrated chromium oxide does not change and is still a mixed phase structure of Cr(OH)3 and CrOOH, and a single α-CrOOH nanomaterial is not obtained. Compared with Example 1, the material obtained in Comparative Example 1 is still CrO x (OH) 3-2x structure.
[0104] Comparative Example 2
[0105] The basic steps are the same as those in Example 2, except that the amount of hydrated chromium oxide precursor used in step (2) is 6 g.
[0106] In this embodiment, due to the limited capacity of the reactor and the limited active groups of the solution system when the hydrated chromium oxide precursor undergoes a crystal transformation, the crystal transformation of the hydrated chromium oxide precursor is incomplete, and the obtained product is a mixed structure of α-CrOOH and β-CrOOH, and a single α-CrOOH nanomaterial is not obtained. Compared with Example 2, the material obtained in Comparative Example 2 is a mixed crystal nanomaterial.
[0107] Comparative Example 3
[0108] The basic steps are the same as those in Example 3, except that the hydrothermal temperature in step (2) is 120°C.
[0109] In this example, since the temperature of the hydrothermal system is low when the hydrated chromium oxide precursor undergoes a crystal transformation, the α-CrOOH has a low crystallinity and tends to be an amorphous structure, and an α-CrOOH nanomaterial with good crystallinity is not obtained. Compared with Example 3, the material obtained in Comparative Example 3 is amorphous.
[0110] Comparative Example 4
[0111] The basic steps are the same as those of Example 4, except that the hydrothermal temperature in step (1) is 120°C.
[0112] In this embodiment, due to the low temperature of the first hydrothermal reaction, the prepared hydrated chromium oxide has a small particle size and is difficult to filter; after the second hydrothermal reaction, the obtained hydroxyl chromium oxide has an even smaller particle size, making it difficult to achieve complete solid-liquid separation by filtering and centrifugation. Compared with Example 4, Comparative Example 4 cannot achieve complete solid-liquid separation by conventional separation means.
[0113] Comparative Example 5
[0114] The basic steps are the same as those in Example 5, except that the hydrothermal temperature in step (1) is 280°C.
[0115] In this embodiment, the temperature of the first hydrothermal reaction is relatively high, and the obtained hydrated chromium oxide precursor has high crystallinity and large grain growth; after the second hydrothermal reaction, the obtained hydroxylated chromium oxide has relatively large particle size, is easy to filter, and has high crystallinity. Compared with Example 5, the hydroxylated chromium oxide obtained in Comparative Example 5 has a higher degree of crystallinity, but the adsorption performance for bromine is not improved. Too high a hydrothermal temperature increases energy consumption and operational risks.
[0116] Comparative Example 6
[0117] The basic steps are the same as those of Example 6, except that the pH of the mixed solution in step (1) is 3.
[0118] In this embodiment, the hydrated chromium oxide precursor obtained by the first hydrothermal reaction is an amorphous structure, and the chromium oxide hydroxyl prepared from the precursor has a low crystallinity and tends to be an amorphous structure. Compared with Example 6, the chromium oxide hydroxyl obtained in Comparative Example 6 has a lower crystallinity.
[0119] In the above embodiment, compared with the case of strong alkaline conditions, the hydrated chromium oxide precursor particles synthesized under weakly acidic conditions are smaller and have a larger specific surface area. Figure 2a and Figure 5a It can be roughly observed that under the same scale, the particle size of the hydrated chromium oxide precursor synthesized under weakly acidic conditions is smaller than that of the hydrated chromium oxide precursor synthesized under strongly alkaline conditions. In addition, the hydroxylated chromium oxide prepared using the hydrated chromium oxide precursor synthesized under weakly acidic conditions has a better adsorption effect. Figure 2b and Figure 5b It can be seen that the hydroxy chromium oxide prepared by the hydrated chromium oxide precursor synthesized under weakly acidic conditions has a uniform hexagonal morphology; the hydroxy chromium oxide prepared by the hydrated chromium oxide precursor synthesized under strongly alkaline conditions has a regular hexagonal morphology, but the particle size distribution is not uniform enough.
[0120] The adsorption effect of the above cases is as follows Fig.10 In summary, through a series of experiments, it was verified that -1 In the mixed solution of KBr and KI (in terms of Br ions and I ions), α-CrOOH can effectively remove bromide ions from aqueous solution under different pH and adsorbent dosage conditions, and basically does not adsorb iodide ions under the same adsorption conditions. Experiments have shown that chromium hydroxide adsorbent has the ability to selectively adsorb bromine in aqueous solution, and has a certain universality in the application of bromine extraction from brine.
[0121] The various aspects, embodiments, features and examples of the present invention should be considered as illustrative in all aspects and are not intended to limit the present invention, the scope of the present invention is defined only by the claims. Other embodiments, modifications and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.
[0122] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.
[0123] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made without departing from the spirit and scope of the present invention and that the elements of the embodiments may be replaced by substantial equivalents. In addition, many modifications may be made without departing from the scope of the present invention to adapt specific circumstances or materials to the teachings of the present invention. Therefore, it is not intended herein to limit the present invention to the disclosed specific embodiments for performing the present invention, but it is intended that the present invention will include all embodiments within the scope of the appended claims. In addition, unless specifically stated, any use of the terms first, second, etc. does not indicate any order or importance, but rather uses the terms first, second, etc. to distinguish one element from another.
Claims
1. A method for preparing a chromium oxyhydroxide adsorbent for selective bromine extraction, characterized in that: include: A mixed system including a soluble chromium salt, a reducing agent, a mineralizer and water is subjected to a first hydrothermal reaction to obtain a hydrated chromium oxide precursor; The hydrated chromium oxide precursor is subjected to a second hydrothermal reaction in a strongly acidic solution with a pH value of ≤3 to prepare a chromium oxide hydroxyl adsorbent.
2. The preparation method according to claim 1, characterized in that: Specifically include: At least the soluble chromium salt, the reducing agent, the mineralizer and the water are mixed evenly, and the pH value is adjusted to 4.5 to 14, and then a first hydrothermal reaction is carried out at 120° C. to 260° C. to obtain a hydrated chromium oxide precursor CrO x (OH) 3-2x , where x is between 0 and 1.
3. The preparation method according to claim 2, characterized in that: The temperature of the first hydrothermal reaction is 120°C to 260°C, preferably 180°C to 240°C; and / or the time of the first hydrothermal reaction is 2 to 24 hours; and / or the mass ratio of the soluble chromium salt, the reducing agent and the mineralizer is (1 to 1.5): (1.2 to 0.2): (0.1 to 0.5); and / or the pH value ranges from 6 to 9.
4. The preparation method according to claim 1 or 2, characterized in that: The soluble chromium salt includes a hexavalent chromium salt, and the hexavalent chromium salt includes any one or a combination of two or more of chromic acid, potassium chromate, potassium dichromate, ammonium chromate, ammonium dichromate, chromium chromate, chromic anhydride, sodium chromate, and sodium dichromate; and / or, the reducing agent includes any one or a combination of two or more of starch, urea, ascorbic acid, PVA, sodium persulfide, ethylene glycol, acetic acid, citric acid, methanol, and anhydrous ethanol; and / or, the mineralizer includes any one or a combination of two or more of sodium carbonate, sodium bicarbonate, and sodium hydroxide.
5. The preparation method according to claim 1, characterized in that: Specifically include: After the hydrated chromium oxide precursor and the strong acid solution are uniformly mixed, a second hydrothermal reaction is carried out at 160° C. to 240° C., thereby preparing the chromium oxide hydroxyl adsorbent.
6. The preparation method according to claim 5, characterized in that: The temperature of the second hydrothermal reaction is 160°C to 240°C, preferably 200°C to 240°C; and / or, the time of the second hydrothermal reaction is 2 to 24 hours, preferably 2 to 12 hours; and / or, the pH of the strongly acidic solution is 0.1 to 3; and / or, the solid-liquid ratio of the hydrated chromium oxide precursor to the strongly acidic solution is 0.01:1 to 0.1:1; and / or, the strongly acidic solution includes at least any one of hydrochloric acid, sulfuric acid, nitric acid, perchloric acid, and chromic acid.
7. A chromium oxyhydroxide adsorbent prepared by the preparation method according to any one of claims 1 to 6.
8. The chromium oxyhydroxide adsorbent according to claim 7, characterized in that: The chromium oxyhydroxide adsorbent has a crystal form of trigonal α-CrOOH; and / or, the mass fraction of chromium in the chromium oxyhydroxide adsorbent is 60.5-68.6%; and / or, the micropores of the chromium hydroxide adsorbent have a pore size of 1 to 2 nm, and the mesopores have a pore size of 12.97 to 14.27 nm; and / or, the particle size of the chromium hydroxide adsorbent is 50 to 100 nm; and / or, the specific surface area of the chromium hydroxide adsorbent is 53.68 to 55.04 m 2 / g; and / or, the morphology of the chromium oxyhydroxide adsorbent includes regular hexagonal flakes.
9. Use of the chromium oxyhydroxide adsorbent according to any one of claims 7 to 8 in adsorbing bromide ions; preferably, the use comprises: The chromium oxyhydroxide adsorbent is used to concentrate seawater or brine to extract bromine or remove bromine from groundwater.
10. A method for removing bromide ions in an aqueous system, characterized in that: include: The chromium oxyhydroxide adsorbent according to any one of claims 7 to 8 is used to adsorb bromide ions in the aqueous phase system.